2014
DOI: 10.1590/1089-6891v15i422937
|View full text |Cite
|
Sign up to set email alerts
|

Utilização da silagem de restos culturais do abacaxizeiro em substituição à silagem de cana-de-açúcar na alimentação de ovinos

Abstract: Avaliou-se a taxa de desaparecimento e a digestibilidade da silagem de restos culturais do abacaxizeiro (SRA) em substituição à silagem de cana-de-açúcar aditivada com 0,5% de ureia (SC) na alimentação de ovinos. Foram utilizados cinco cordeiros, raça Santa Inês, alocados em delineamento experimental quadrado latino 5X5, alimentados com dietas contendo 13,5% de PB e 63,0% de NDT. Foram avaliadas cinco dietas definidas da seguinte forma: 100% de SRA: 0% SC (100A); 75% SRA: 25% SC (75A); 50% SRA: 50% SC (50A); 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
(10 reference statements)
0
7
0
1
Order By: Relevance
“…periods of scarcity, obtaining an alternative food for the animals becomes of great importance for the intensive farming system, reducing feed costs. Current studies and work on the use of pineapple crop residues have shown very promising results with the use of silage as a form of forage storage and with good results from its use in feeding ruminants (Fagundes & Fagundes, 2010;Lallo et al, 2003;Prado et al, 2003;S. C. Santos et al, 2014), as well to minimize environmental contamination with the large amount of vegetable waste produced (M. Santos, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…periods of scarcity, obtaining an alternative food for the animals becomes of great importance for the intensive farming system, reducing feed costs. Current studies and work on the use of pineapple crop residues have shown very promising results with the use of silage as a form of forage storage and with good results from its use in feeding ruminants (Fagundes & Fagundes, 2010;Lallo et al, 2003;Prado et al, 2003;S. C. Santos et al, 2014), as well to minimize environmental contamination with the large amount of vegetable waste produced (M. Santos, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Brazil occupies a prominent position in pineapple growing as the third largest world producer, with almost 1.5 billion fruits harvested from approximately 64,147 ha of cultivated area (Instituto Brasileira de Geografia e Estatística [IBGE], 2022). The industrialization of tropical fruit farming has provided enormous surpluses of byproducts, which in the natural or processed form could contribute a significant portion to ruminant nutrition (Cunha et al, 2009;S. C. Santos et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The expansion of fruit farming combined with investments in agroindustries results in increased amounts of byproducts, which may increase operating costs for companies and potentially become an environmental problem depending on how the byproducts are discarded (Santos et al, 2014). Brazil is among the largest pineapple-producing countries (Ananas comosus (L.) Merril) in the world, contributing 9.89% of global production (CONAB, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Although few studies have been carried out using pineapple crop waste in ruminant feeding, they have shown very promising results, apparent digestibility of dry matter (DM) of 665.80 g/kg, and digestibility of neutral detergent fiber of 548.6 g/kg (Santos et al, 2014). Thus, we hypothesized that pineapple crop waste can be used as a roughage source in sheep feeding in times of feed scarcity.…”
Section: Introductionmentioning
confidence: 99%
“…A industrialização da fruticultura tropical tem propiciado importantes quantidades de resíduos ou de subprodutos, que in natura ou beneficiados, possuem potencial de contribuir de forma expressiva na alimentação de ruminantes (Santos et al, 2014), consequentemente, se faz necessário avaliar esses substratos no intuito de se determinar níveis de inclusão adequados, baseando-se nos aspectos nutricionais, digestivos, comportamentais e na viabilidade econômica destas diferentes alternativas.…”
Section: Introductionunclassified